A Controller for Si MZI-Based Spanke-Benes Optical Switch Fabric With Automatic Calibration Capability - Hyun-Kyu Kim; Yongjin Ji; Kihun Kim; Woo-Young Choi (IEEE Photonics Journal, 2023)
We demonstrate an FPGA-based controller for Si MZI-based Spanke-Benes 4 × 4 optical switch fabric that can automatically calibrate each individual switching cell and select the desired routing configuration. In order to minimize the power consumption for optical switching operation, the optimal heater voltages for the cross and the bar state of each switching cell is determined during the calibration. The operation of our controller is successfully verified with a Si MZI-based Spanke-Benes 4 × 4 optical switch.